Ratio of supplement for Saccharum edule Hassk waste ensilage - Jujun Ratnasari; Billyardi Ramdhan; Reny Sukmawani (International Journal of Advances in Applied Sciences, 2023)
Saccharum edule Hassk (Terubuk) is a plant of the Poaceae family that after consuming its flowers as vegetables, Saccharum edule Hassk waste in the form of leaves and stems can be used as alternative animal feed. Improving the nutrition of crushed waste as an alternative feed can be done through ensilage using several mixed ingredients that can maximize the fermentation process. The study aimed to analyze the effect of differences in the ratio of starter microbial with a mixture of silage, such as molasses and rice bran, on the quality of the Saccharum edule Hassk waste silage. The research was conducted using leaf and stem material using the anaerobic fermentation method. The ratio of microbes, molasses, and rice bran used was 0.00067%:2%:4% (S1), 0.0008%:3%:6% (S2), and 0.001%:4%:8% (S3). The fermentation time was 14, 21, and 28 days. The results obtained showed that pH <4 was achieved by S1, S2, and S3, at 21 and 28 days of fermentation. Fleigh value (NF) of S1 and S2 at 21 days of fermentation was 72.47% while in S3 it was 72.20%. The NF at 28 days of fermentation was 85.53% in S1, and 85. 67% in S2 and S3. The highest protein content is in S2 at 10.37 ± 0.69% (p>0.05) in a fermentation time of 21 days.